Phenotypic Plasticity of Winter Wheat Heading Date and Grain Yield across the US Great Plains. Issue 5 (1st September 2016) - Grogan, Sarah M.; Anderson, Josh; Baenziger, P. Stephen; Frels, Katherine; Guttieri, Mary J.; Haley, Scott D.; Kim, Ki‐Seung; Liu, Shuyu; McMaster, Gregory S.; Newell, Mark; Prasad, P. V. Vara; Reid, Scott D.; et al.
Abstract : Phenotypic plasticity describes the range of phenotypes produced by a single genotype in different environments. We quantified the extent of phenotypic plasticity (evaluated as responsiveness to varying environmental conditions) of thermal time to heading and grain yield in 299 hard winter wheat ( Triticum aestivum L.) genotypes from the US Great Plains. The genotypes, which included advanced breeding lines and recent and historic cultivars, were evaluated in 11 environments in 2011–2012 and 2012–2013. The average number of days from 1 January to heading across environments ranged from 109 to 150, and the cumulative growing degree days (GDD) from 1 January to heading ranged from 730 to 1112 GDD. Environmental mean grain yield varied from 1.3 to 5.3 Mg ha −1 . Plasticity of GDD (GDDP) was strongly correlated with GDD ( r = 0.81, P < 0.001), especially maximum GDD ( r = 0.90, P < 0.001) across environments, indicating genotypes with greater plasticity developed later, especially within the earliest environments. Plasticity of GDD was negatively associated with yield ( r = −0.58, P < 0.001) and therefore detrimental in the germplasm and environments evaluated. Yield plasticity of a genotype was positively correlated with its maximum ( r = 0.80, P < 0.001) and minimum ( r = 0.33, P < 0.001) grain yield across environments, indicating greater plasticity was favorable under optimal conditions, without a penalty under low‐yielding conditions. More than a century of wheat breeding in this region suggests GDDP has declined and yield plasticity has increased at similar rates. This is encouraging because it indicates the favorable plasticity traits (high yield plasticity, low GDDP) have been selected for indirectly and would respond to further selection.